2010
DOI: 10.1563/aaid-joi-d-09-00100
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Ridge Augmentation Utilizing a Composite Graft of Demineralized Freeze-Dried Allograft, Mineralized Cortical Cancellous Chips, and a Biologically Degradable Thermoplastic Carrier Combined With a Resorbable Membrane: A Retrospective Evaluation of 73 Consecutively Treated Cases From Private Practices

Abstract: Ridge deficiency is an unfortunate obstacle in the field of implant dentistry. Many techniques are available to rebuild the deficient ridge. Some of these techniques are associated with significant morbidity and often require a second surgical site. With the advent of guided bone regeneration (GBR), one may now graft the deficient ridge with decreased morbidity and without a second surgical site. The purpose of this retrospective consecutive case series from 5 private practices is to report on the outcomes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 24 publications
(17 reference statements)
0
19
0
1
Order By: Relevance
“…As compared to onlay grafts, particulate grafts require additional materials to ensure space maintenance and graft containment such as barrier membranes, tenting screws, and/or graft binders, while onlay grafts are self-contained and provide an inherent ability to support the soft tissue [4]. Therefore, onlay autografts are the best grafting material for ridge augmentation procedure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As compared to onlay grafts, particulate grafts require additional materials to ensure space maintenance and graft containment such as barrier membranes, tenting screws, and/or graft binders, while onlay grafts are self-contained and provide an inherent ability to support the soft tissue [4]. Therefore, onlay autografts are the best grafting material for ridge augmentation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, harvesting graft from extraoral sources requires general anaesthesia and hospital admission with a longer healing period which can be avoided when an intraoral site is chosen [3, 4]. Several studies have shown that intraoral autogenous grafts have a lower rate of resorption and better revascularization compared to iliac crest grafts [4]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Because of this, several factors must be taken into consideration when choosing the donor site, including the location of the recipient bed, the quality and quantity of the required bone graft, and the potential for surgical complications. 8 Guided bone regeneration (GBR) is a procedure often employed for an implant site that presents buccal dehiscence or fenestration defects. 9 A barrier membrane is necessary for this procedure.…”
Section: Introductionmentioning
confidence: 99%